ICT-based needs analysis of learning arts and culture in middle school at Sunggal - Batubara, Qothrun Nada Ma'ruf (Research in Education and Technology (REGY), 2023)
The use of ICT has begun to be developed and implemented at almost all levels of education, from elementary, junior high school/middle school to senior high school education. Precisely at Sunggal 1 Public Middle School (SMP Negeri 1 Sunggal) is one of the schools that maximizes the use of ICT. The needs assessment was implemented with the aimed of improving the planning of further educational programs related to the learning process, starting from planning, development, utilization, and management to assessment. The data collection technique used in this research was by distributing questionnaires to students and teachers, followed by conducting classroom observations. This research used a Likert scale calculation method and qualitative descriptive. Teachers predominantly use lecture and discussion methods during the learning process. Assisted by projector technology and PowerPoint slide media, offline learning is more fun.